-3(x-7)=2(3x-5)

Simple and best practice solution for -3(x-7)=2(3x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-7)=2(3x-5) equation:


Simplifying
-3(x + -7) = 2(3x + -5)

Reorder the terms:
-3(-7 + x) = 2(3x + -5)
(-7 * -3 + x * -3) = 2(3x + -5)
(21 + -3x) = 2(3x + -5)

Reorder the terms:
21 + -3x = 2(-5 + 3x)
21 + -3x = (-5 * 2 + 3x * 2)
21 + -3x = (-10 + 6x)

Solving
21 + -3x = -10 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
21 + -3x + -6x = -10 + 6x + -6x

Combine like terms: -3x + -6x = -9x
21 + -9x = -10 + 6x + -6x

Combine like terms: 6x + -6x = 0
21 + -9x = -10 + 0
21 + -9x = -10

Add '-21' to each side of the equation.
21 + -21 + -9x = -10 + -21

Combine like terms: 21 + -21 = 0
0 + -9x = -10 + -21
-9x = -10 + -21

Combine like terms: -10 + -21 = -31
-9x = -31

Divide each side by '-9'.
x = 3.444444444

Simplifying
x = 3.444444444

See similar equations:

| 28=2+2a | | 2(x-8)-5(x+6)=2 | | -3x+21=6x-10 | | 4a-3b+2c= | | 100=4r | | M+(-19)=40 | | 6x+6=9x-6 | | (ab+4a+-6)+(ab+6)= | | 7(b+2)-13b=2(b-1)+6 | | 585.00+0.13x=525.00+0.21x | | x^2-2x+y^2-2y-3=0 | | X^3+7x-x-7=0 | | 2x-6=2(2-8)+10 | | 2x+6=y+4 | | 2x^2+-4x=0 | | 525.00+0.21x=585 | | 3x-2(5y-6)=8 | | 10(z+3)=5(z-8) | | 5-(x+3)=10 | | -t+15=2 | | 3u+147=180 | | x(x+1)=1024 | | x=15+7x-81 | | -7+3+-5= | | 6x-19=10x-79 | | 10m=(3m-11)-17 | | -2x^3+19X^2-38x+21=0 | | z=2z-68 | | 3x-11=2(x-3)-8 | | -26+17= | | 1=-3xy | | 4t+5=2 |

Equations solver categories